Determinants of Malaysia gross domestic product (GDP) / Dayang Nur Arfiny Awg Sahari - Awg Sahari, Dayang Nur Arfiny (2021)
According to the FMT news article, Malaysia Gross Domestic Product (GDP) drop by 5.6% in year 2020, in which it is the lowest GDP since Asian Financial Crisis 1998. The mainly reason is must be the enforcement of the movement control order (MCO) since Mac. As we know, GDP is showing the health of Malaysia economy status. In this research, I studied the relationship between GDP with six macroeconomic variable which are interest rate, inflation rate, net export, income level, tax rate and unemployed rate. In order to perform and determine the hypotheses, I used Ordinary Least Square (OLS) regression, which is Multiple Regression Equation method by using EViews 1 1 Student Version. Through this methodology, I expect to obtain positive and negative relationship, also the significance of these macroeconomic variables toward GDP in Malaysia. The findings of this research may assist future investors in formulating and renewing their investment strategy in order to minimize potential risk, particularly during bad economic performance.